(untitled) (Veterinary Science, 2017)
Economic problems of great complexity should be approach in an interdisciplinary way. The veterinarian makes his own contribution from the professional activity mainly associated to animal production. The close relationship among production, economy and environmental impacts an additional element in decision making both in public and private spheres. The objet of this work is to present a methodological revision of procedures in order to figure out the human activities’ impacts upon environment froman economic point of view. Theoretical bases an basic assumptions changes and procedures used are described. Different evaluation techniques on environment changes and procedures used are described. As a conclusion a critical analysis on the advantages and disadvantages of different techniques is made